A Putative Mechanism of Age-Related Synaptic Dysfunction Based on the Impact of IGF-1 Receptor Signaling on Synaptic CaMKIIα Phosphorylation - Ogundele, Olalekan M.; Pardo, Joaquin; Francis, Joseph; Goya, Rodolfo G.; Lee, Charles C. (Frontiers in Neuroanatomy, 2018)
Insulin-like growth factor 1 receptor (IGF-1R) signaling regulates the activity and phosphorylation of downstream kinases linked to inflammation, neurodevelopment, aging and synaptic function. In addition to the control of Ca2+ currents, IGF-1R signaling modulates the activity of calcium-calmodulin-dependent kinase 2 alpha (CaMKIIα) and mitogen activated protein kinase (MAPK/ErK) through multiple signaling pathways. These proteins (CaMKIIα and MAPK) regulate Ca2+ movement and long-term potentiation (LTP). Since IGF-1R controls the synaptic activity of Ca2+, CaMKIIα and MAPK signaling, the possible mechanism through which an age-dependent change in IGF-1R can alter the synaptic expression and phosphorylation of these proteins in aging needs to be investigated. In this study, we evaluated the relationship between an age-dependent change in brain IGF-1R and phosphorylation of CaMKIIα/MAPK. Furthermore, we elucidated possible mechanisms through which dysregulated CaMKIIα/MAPK interaction may be linked to a change in neurotransmitter processing and synaptic function. Male C57BL/6 VGAT-Venus mice at postnatal days 80 (P80), 365 and 730 were used to study age-related neural changes in two brain regions associated with cognitive function: hippocampus and prefrontal cortex (PFC). By means of high throughput confocal imaging and quantitative immunoblotting, we evaluated the distribution and expression of IGF-1, IGF-1R, CaMKIIα, p-CaMKIIα, MAPK and p-MAPK in whole brain lysate, hippocampus and cortex. Furthermore, we compared protein expression patterns and regional changes at P80, P365 and P730. Ultimately, we determined the relative phosphorylation pattern of CaMKIIα and MAPK through quantification of neural p-CaMKIIα and p-MAPK/ErK, and IGF-1R expression for P80, P365 and P730 brain samples. In addition to a change in synaptic function, our results show a decrease in neural IGF-1/IGF-1R expression in whole brain, hippocampus and cortex of aged mice. This was associated with a significant upregulation of phosphorylated neural MAPK (p-MAPK) and decrease in total brain CaMKIIα (i.e., CaMKIIα and p-CaMKIIα) in the aged brain. Taken together, we showed that brain aging is associated with a change in neural IGF-1/IGF-1R expression and may be linked to a change in phosphorylation of synaptic kinases (CaMKIIα and MAPK) that are involved in the modulation of LTP.